PRODUCTION PROCESS COST ANALYSIS IN TEXTILE INDUSTRY WHICH USE COAL AS COMPLIMENTER OF OIL FUEL IN WEST JAVA PROVINCE - Rikha Agustien , Wulan
As the source of energy for economical activities, the existence of fuels is very important. Lack of petroleum deposits have caused the oil fuel expenses to increase for the last recent years and it has an impact on industry economy, specially in textile industry. To supply the energy consumption, textile industry depends a lot on oil fuel. The energy expenses is about 40 % from the total expenses and the fuel consumption is about 30-40% from the energy expenses. Some textile industries have been bankrupt due to the high production cost. Therefore, to avoid bankruptcy, they should change the fuel that costs cheaper than oil fuel, the fuel supplies should be abundant, the fuel should have minimal effects on environment, and is easy to be handled. Coal stands for all those requirements. Based on 5 variables costs, which are : equipment investment, fuel consumption, waste handling, maintenance and transportation, coal is very much effective to reduce the production process cost. The efficacy level for coal using cost is 65-90 %, means that the total production cost decreases 7-14 % from the previous total cost (using oil fuel). The efficacy of coal usage reach optimum point for textile industries whill have production capacity of 450 ton and 300 ton.. The amount of coal consumption to produce 1 ton textile is greater than the amount of oil fuel consumption, but it will not influence the efficacy level because coal costs cheaper than oil fuel. As the coal calorivic value goes high, the amount of coal will not decrease. For coal with 6500 kcal/kg, 2 ton of coal will be needed to produce 1 ton textile. 2,5 ton of coal will be needed to produce 1 ton textile if the coal calorivic value is 6000 kcal/kg and 6300 kcal/kg.Yet, the use of coal with high calorivic value is not the optimum efficacy level, for the optimum efficacy level is on 5800 kcal/kg and 5500 kcal/kg. Based on the amount of calories to produce 1 ton textile, the optimum efficacy level should be reached by using coal with high calorivic value. But, in this case, equipments will also influence the efficacy level.